2017
DOI: 10.1103/physrevd.96.024051
|View full text |Cite
|
Sign up to set email alerts
|

Emergent gravity of fractons: Mach’s principle revisited

Abstract: Recent work has established the existence of stable quantum phases of matter described by symmetric tensor gauge fields, which naturally couple to particles of restricted mobility, such as fractons. We focus on a minimal toy model of a rank 2 tensor gauge field, consisting of fractons coupled to an emergent graviton (massless spin-2 excitation). We show how to reconcile the immobility of fractons with the expected gravitational behavior of the model. First, we reformulate the fracton phenomenon in terms of an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 51 publications
5
134
0
Order By: Relevance
“…Various other aspects of the dynamics were studied in [13], such as an anomalous exponent in the "tail" of the ballistically spreading peak. It was also shown that fractons could attract each other under random unitary evolution, consistent with the gravitational analysis of Reference [14].…”
Section: B Localization Of Fractons In One Dimensionsupporting
confidence: 80%
See 1 more Smart Citation
“…Various other aspects of the dynamics were studied in [13], such as an anomalous exponent in the "tail" of the ballistically spreading peak. It was also shown that fractons could attract each other under random unitary evolution, consistent with the gravitational analysis of Reference [14].…”
Section: B Localization Of Fractons In One Dimensionsupporting
confidence: 80%
“…At this level, it can already schematically be seen that fractons exert an effective attraction on each other, since a pair of fractons will slow down as they begin to move apart. This logic can be placed on firmer footing by studying the semi-classical equations of motion of the system, which indicate that a fracton moves along geodesic-like curves of an effective geometry dictated by the positions of all other fractons in the system [14]. In this sense, the interaction between fractons is purely geometric, just as in general relativity.…”
Section: A Gravitation In Fracton Systemsmentioning
confidence: 99%
“…As discussed in earlier work 16 , a fracton will acquire finite mobility in the presence of a finite-density distribution of other fractons. In the presence of fracton density n, the typical velocity of a fracton will behave as v ∼ n. Once again, we expect that thermalization will only occur after fractons have moved a distance on the order of the interparticle spacing, n −1/3 .…”
Section: E Thermalizationmentioning
confidence: 82%
“…We expect the same qualitative physics should hold for any U (1) model with these basic characteristics. The model we will work with has been studied in some detail in previous literature [1][2][3]16 . We will review the most important features of this phase here, though we refer the reader to these previous works for more details.…”
Section: A Review Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation